Healthy vs. osteoarthritic hips: A comparison of hip, pelvis and femoral parameters and relationships using the EOS® system. Issue 2 (February 2015) - Bendaya, S.; Lazennec, J.Y.; Anglin, C.; Allena, R.; Sellam, N.; Thoumie, P.; Skalli, W.
Abstract Background Osteoarthritis is a debilitating disease, for which the development path is unknown. Hip, pelvis and femoral morphological and positional parameters relate either to individual differences or to changes in the disease state, both of which should be taken into account when diagnosing and treating patients. These have not yet been comprehensively quantified. Previous imaging studies have been limited by a number of factors: supine rather than standing measurements; high radiation dose; a limited field of view; and 2D rather than 3D measurements. EOS®, a new radiographic imaging modality that acquires simultaneous frontal and lateral (sagittal) X-ray images of the full body, allows 3D reconstruction of the hip, pelvis and lower limb. The aim of the study was to explore similarities and differences between healthy and osteoarthritis groups. Methods Two groups of subjects, 30 healthy and 30 with hip osteoarthritis, were assessed and compared for pelvic, acetabular and femoral parameters in the standing position. Findings There were not only significant differences between groups but also considerable overlap amongst the individuals. Sacral slope, acetabular angle of Idelberger and Frank, femoral mechanical angle and femoral head eccentricity as well as right–left asymmetries in centre-edge acetabular angle and femoral head diameter were higher on average in osteoarthritic patients compared to healthy subjects, whereas acetabular abduction was lower in the osteoarthritic group (P < 0.05). Correlations were identified between key parameters in both groups. Interpretation Differences between the groups suggest either degenerative changes over time or inherent differences between individuals that may contribute to the disease progression. These data provide a basis for longitudinal and post-surgery studies. Due to the considerable variability amongst individuals and the considerable overlap between groups, patients should be evaluated individually and at multiple joints when planning hip, knee and spine surgery.